Microwave-induced degradation of Congo red dye in the presence of 2D Ti3C2Tx MXene as a catalyst - Salma M. El-Mas; Mohamed A. Hassaan; Gehan M. El-Subruiti; Abdelazeem S. Eltaweil; Ahmed El Nemr (Scientific Reports)
Abstract In this research, the degradation of Congo red (CR) dye, as an organic pollutant in water, was investigated using microwave-induced reaction technology. This technology requires a microwave-absorbing catalyst and the 2D Ti3C2Tx MXene was synthesized for that purpose. The synthesized catalyst was characterized using XRD, SEM, TEM, EDX, BET, and XPS techniques. Results showed that the prepared 2D Ti3C2Tx MXene with a dosage of 50 mg degraded CR dye with an initial concentration of 25 ppm in an aqueous solution with a degradation percentage of approximately 99% in only 6 min. The parameters studied were catalyst dosage and initial CR dye concentration, which were found to have significant impacts on the degradation rate. When the catalyst dosage was increased significantly, the degradation rate increased significantly. On the other hand, when increasing the initial CR dye concentration, the degradation rate decreased. The degradation kinetics were studied, and the reaction followed the pseudo-first-order model. The rate constants obtained ranged from 0.04 to 0.83 min−1, varying according to the used catalyst dosage and initial CR dye concentration. The catalyst was stable and could be reused for up to five catalytic cycles without losing its degradation efficiency. The active species participating in the degradation process were determined using scavengers such as benzoquinone, Na-EDTA, and isopropyl alcohol. Optimization of the degradation parameters using a response surface methodology study concluded that a maximum degradation percentage could be reached when employing 35.30 mg of 2D Ti3C2Tx MXene and 29.07 ppm of CR dye solution.